2007
DOI: 10.1007/s12070-007-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomas of head and neck — A 10 yrs experience

Abstract: Abstract38 cases of sarcoma of head and neck region were analysed in a retrospective way in relation to age, anatomic location, histological, clinical profi le, and surgical approaches. Compared to other types of head and neck neoplasms, such as squamous cell carcinoma, soft tissue sarcomas have low rates of regional metastases. However the biological behaviour of soft tissue sarcoma is more aggressive specially in paediatric age group. In the present series, CT scan was considered as the primary modality of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…In this study, more than half of the involved patients with the head and neck sarcomas (56%) were females, which is in line with the findings by Bree et al (27) , although in several other studies (23,(28)(29)(30)(31) men have been reported to be affect-Discussion neck neoplasms (e.g., squamous cell carcinoma), soft tissue sarcomas have a lower rate of regional metastasis. (39) In this study, only 2 cases (3.4%) had metastasis to other parts of the body, whereas in a study conducted by Tajudeen et al (9) metastasis to lymph nodes was 6.5% and neural invasion was observed in 6.5% of the cases. Salcedo-Hernández et al (5) reported 50% of soft tissue sarcomas of the head and neck involving metastasis.…”
Section: Resultscontrasting
confidence: 55%
“…In this study, more than half of the involved patients with the head and neck sarcomas (56%) were females, which is in line with the findings by Bree et al (27) , although in several other studies (23,(28)(29)(30)(31) men have been reported to be affect-Discussion neck neoplasms (e.g., squamous cell carcinoma), soft tissue sarcomas have a lower rate of regional metastasis. (39) In this study, only 2 cases (3.4%) had metastasis to other parts of the body, whereas in a study conducted by Tajudeen et al (9) metastasis to lymph nodes was 6.5% and neural invasion was observed in 6.5% of the cases. Salcedo-Hernández et al (5) reported 50% of soft tissue sarcomas of the head and neck involving metastasis.…”
Section: Resultscontrasting
confidence: 55%
“…Ocular symptoms include diplopia, unilateral tearing, and fullness of lids, orbital pain and also exophthalmos. Facial symptoms include paraesthesia over the infraorbital nerve, swelling and pain over cheek and facial asymmetry as seen in our case [1,3]. This case is presented for its uniqueness of occurrence at a comparatively younger age, site and aggressive nature of presentation.…”
Section: Discussionmentioning
confidence: 61%
“…Sarcomas are rare tumours usually heterogeneous by nature, largely originating from the embryonic mesoderm accounting for less than 1% of all head and neck primary cancers [1]. Numerous studies have reported that oral sarcomas represent 0.14%-27.7% of all head and neck cancers suggestive of rarity of the tumour [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations